The effectiveness of prediction and clairvoyance and its functions in the inner space (Al-Academy, 2023)
The research dealt with the effectiveness of prediction and foresight in design as a phenomenon that plays a role in the recipient's engagement with the design, as it shows the interaction between the recipient and the interior space. The designer is keen to diversify his formal vocabulary in a way that secures visual values that call for aesthetic integration, as well as securing mental and kinetic behavioral understanding in the interior space.As the designer deals with a three-dimensional space that carries many visual scenes, the designer should not leave anything from it without standing on it with study and investigation, and puts the user as a basic goal as he provides interpretive data through prediction and foresight that leads the sensory and aesthetic thought of the visual scenes, the subject of predicting what will happen in the future in terms of ideas Thoughtful and innovative visions